Bifid cardiac apex in Pallister-Killian syndrome : case report = Bifidno srce u sindromu Pallister-Killian : prikaz slučaja - Barišić, Anita (Array, 2020)
Aim: Pallister-Killian syndrome (PKS) is a rare chromosomal disorder, caused by tissue-limited mosaicism for an isochromosome 12p. Prenatal diagnosis of PKS is generally incidental. Although clinical presentation of PKS varies, cytogenetic findings are constant, and include a tetrasomy of chromosome 12p. We report a case of prenatally diagnosed PKS with unique dysmorphic feature: bifid cardiac apex, a type of morphology that has not been documented before. Case presentation: Our patient was the 38-year-old pregnant woman who underwent amniocentesis. Cytogenetic analysis of amniotic fluid detected a mosaic karyotype with a supernumerary chromosome (SMC) in 64 % of fetal amniocytes. To determine the chromosomal origin of SMC, fluorescence in situ hybridization was performed and tetrasomy 12p was confirmed: mos 47,XY,+mar[18]/46,XY[10].ishi(12p)(8M16/SP6++,CEP12+,VIJyRM2196-). Ultrasound examination showed a fetus with cleft lip, echogenic focus in the left ventricle of the heart and shortened fetal long bones. After receiving a genetic counseling for PKS, the woman requested a termination of pregnancy. A postmortem inspection of the fetus revealed a complex heart anomaly that includes bifid cardiac apex and ventricular septal defect. Conclusions: This report expands the clinical manifestations of PKS with a unique feature of bifid cardiac apex, and highlights the targeted prenatal diagnosis of PKS if specific ultrasound markers are present.